Dynamic Interaction between Student Learning Behaviour and Learning Environment: Meta-Analysis of Student Engagement and Its Influencing Factors - Jian Li; Eryong Xue (Behavioral Sciences, 2023)
Student engagement plays a significant role in promoting student learning outcomes in the higher education context. The goal of this meta-analysis was to investigate factors influencing student engagement in higher education institutions in different contexts. The meta-analysis integrated data from 93,188 participants and 148 effects across studies to address this issue. The meta-analysis revealed 14 factors affecting students’ learning participation. The classification was based on internal and external factors, aiming to explore the main factors influencing students’ intention, behavior, and process of learning participation. The external influencing factors with moderate correlations were the teacher-student relationship (R = 0.456, p < 0.001) and positive teacher behavior (R = 0.419, p < 0.001). Additionally, the main external influencing factors were partnership (R = 0.174, p < 0.001), environmental support (R = −0.028), negative teacher behavior (R = −0.064), and negative learning behavior (R = −0145), which were all negatively correlated with learning participation. The results also indicated that factors influencing student engagement can be divided into two categories: promoting factors and hindering factors. The promoting factors include students’ positive emotion, positive learning behavior, positive teacher behavior, the teacher-student relationship and partnership, students’ learning and thinking ability, the support of learning resources, students’ individual and personality characteristics, and teaching factors. The hindering factors include lack of environmental support, negative student behavior, and negative teacher behavior. Further, conceptual and practical implications are discussed in relation to these findings.